The Effect of Using Brick Filler on Pavement Stability in Benanga Dam Submergence - Liana, Ulwiyah Wahdah Mufassirin; Siregar, Adde Currie; Pratiwi, Dheka Shara; Iqbal, Muhammad (Jurnal Teknik Sipil, 2023)
Benanga Dam is a construction to contain the discharge and store water at Lempake, Samarinda, East Kalimantan. At the beginning of the construction, the capacity is 1.6 million m3 but capacity shrunk until 500.000 m3. Overflow around the dam area, often causes flooding at the Bengkuring’s region. This study aims to determine effect of brick substitution on asphalt pavement in Benanga Dam water. If pavement is submerged, so pavement’s void will fill up water, dissolve materials and decrease pavement quality. The use of bricks to utilize renovation waste and as a substitute for Portland cement because it has pozzolanic properties. Research was conducted by experimental using asphalt Pen 60/70, used coarse and fine aggregate from Palu, consists of 2 variables are 0% and 100% of brick filler. Asphalt concrete mix standard refers to Bina Marga, 2018 and analysis using Marshall method. In this study, innovations used 5.5% of asphalt and 100% of brick have a strength up to 3,190.7 kg and decrease around 5 cm. That asphalt mixture is able to withstand largest traffic load and smaller decrease compared to other mixtures. The Void Filled with Asphalt (VFWA) is 72,7% which is attain requirements and efficient, so the pavement doesn’t have cavity and watertight. Asphalt mixture minimized the occurrence of damage when submerged by flood.